Evaluation of Bone Growth of 0-6 Week Old Native Chicken with Different Levels of Dietary Protein and Lysine Supplementation in the Ration - A. Rizkuna; U. Atmomarsono; D. Sunarti (Jurnal Ilmu dan Teknologi Peternakan, 2014)
This research aimed to study the effect of protein level and lysine supplementation on bone growth of native chicken by the age of 6 weeks. The materials used were unsexed DOC of native chicken with average body weight 25.2 ± 1.0 g. Research was carried out in 2 x 3 factorial arrangement  according to completely randomized design. There were 4 replications for each treatment combination with 10 chickens for each experimental unit. The treatments  were  P1L1 (17% protein  +  0.6% lysine of the ration ), P1L2 (17% protein + 0.7% lysine of the ration), P1L3 (17% protein + 0.8% lysine of the ration ), P2L1 (14% protein + 0.6% lysine of the ration), P2L2 (14% protein + 0.7% lysine of the ration), P2L3 (14% protein + 0.8% lysine the ration). Treatments were applied  starting from the age of  day 1 to 6 weeks of age. Parameters measured were femur length, femur weight and femur bone strength. Data were analyzed by analysis of variance followed by Duncan’s multiple range test at 5% probability level if there was a significant effect of treatment on the parameters. There was a significant interaction (P <0.05) between the level of protein and lysine supplementation affecting the femur length and femur bone weight, but there was no  interaction (P> 0.05) effects on the femur bone strength. Based on these results, it was concluded that the optimal growth of native chicken bones were obtained from the ration containing  17% protein and 0.8% lysine supplementation.